HUBUNGAN UMUR DAN JENIS KELAMIN TERHADAP KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI PUSKESMAS TEMBILAHAN HULU - Nurul Indah Sari; Ardianti Ardianti (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Acute Respiratory Infection (ARI) is an infectious disease that attacks one or more parts of the respiratory tract, from the nose (upper line) to the alveoli (bottom line) including its adneksa networks, such as sinus tract, the middle ear cavity and pleura. Whereas the causes of respiratory infection in infants are intrinsic factors including age, nutritional status, birth weight, immunization status, sex, whereas extrinsic factors include housing, socio-economic and parental education. The purpose of this study is to determine the relationship between Age And Gender Genesis Against Acute Respiratory Infections (ARI) for Toddlers at UPT Tembilahan Hulu Health Center in 2013-2015. This study is an analytical study using case control design. Sampling was done by systematic random sampling technique. The sample in this study was 636 people were divided into 2 groups : 318 people were as the case group and 318 people that were as the control group. This study used the instrument in the form of a checklist sheet this research was conducted on June 9 to 21, 2014. Results af this research showed that there was a relationship between age and gender on the incidence of respiratory infection in infants with a P value = 0.047 and OR = 1.389 then age gender P value = 0.001 and OR = 1.683. That is why every parent who has a child who is at risk for developing respiratory infection such as age 2-3 years old and the male gender should get more attention, both in terms of the game, daly activities as well as their diet.